2020
DOI: 10.1101/2020.07.20.212852
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep learning detection of informative features in tau PET for Alzheimer’s disease classification

Abstract: BackgroundAlzheimer’s disease (AD) is the most common type of dementia, typically characterized by memory loss followed by progressive cognitive decline and functional impairment. Many clinical trials of potential therapies for AD have failed, and there is currently no approved disease-modifying treatment. Biomarkers for early detection and mechanistic understanding of disease course are critical for drug development and clinical trials. Amyloid has been the focus of most biomarker research. Here, we developed… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…We additionally show that multiple generations of tau radioligands can be integrated into a single framework 7,11 . Earlier deep learning efforts with tau PET have sought to simplify 20 and augment 17 preprocessing steps; and have provided initial proof of feasibility and model interpretation 22 . The main metrics of the models compare similarly with prior deep learning classification tasks that used different sets of PET radioligands, 16,22,46 though comparisons are of course difficult given differences in available clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We additionally show that multiple generations of tau radioligands can be integrated into a single framework 7,11 . Earlier deep learning efforts with tau PET have sought to simplify 20 and augment 17 preprocessing steps; and have provided initial proof of feasibility and model interpretation 22 . The main metrics of the models compare similarly with prior deep learning classification tasks that used different sets of PET radioligands, 16,22,46 though comparisons are of course difficult given differences in available clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that LRP generates more relevant explanations by describing why any individual patient has the disease. Taeho Jo et al [110] implemented LRP to highlight the areas of tau positron emission tomography (PET) that highly contribute to the classification of Alzheimer's disease using 3D-CNN.…”
Section: Machine Learningmentioning
confidence: 99%
“…Extensive evaluations showed that the Auto3DCryoMap can accurately align structural particle shapes and can construct a decent 3D density map from only a few thousand aligned particle images while the existing tools require hundreds of thousands of particle images and reconstruct a better 3D density map. Jo et al published “Deep learning detection of informative features in tau PET for Alzheimer’s disease classification” [ 9 ], in which the authors developed a deep learning-based framework to identify informative features for Alzheimer’s disease classification using tau position emission tomography scans. By applying five-fold cross-validation, the authors demonstrated their method yielded an accuracy of 90.8%.…”
Section: Imaging and Machine Learningmentioning
confidence: 99%